PARAMETER PENYALAHGUNAAN KEWENANGAN YANG MERUGIKAN KEUANGAN NEGARA DALAM TINDAK PIDANA KORUPSI - Naftali Gakur; Hufron Hufron (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Corruption is one of the high-level crimes (ordinary crime), because corruption is not only detrimental to state finances, but also harms the wider community. Corruption crimes themselves are mostly committed by people who have positions or authorities, such as ASN (State Civil Apparatus), Regents, Governors, and other government officials. With the position or position and authority possessed, government officials have many ways and opportunities to abuse their authority in committing corruption crimes. There are two authorities of government officials, namely bound authority and free authority (discretion). Parameters to find out whether the actions carried out by government officials are a form of abuse of authority in corruption crimes or not, namely using laws and regulations consisting of laws and regulations consisting of laws, provincial regulations or regency/city regulations, especially for bound authority, while for free authority the parameters are good general principles such as principles of good governance (AAUPB) and general principles others outside the AAUPB; general principles of state governance (AAPN); Principles of State Governance (APPN); Principles of Village Government Management (APPD).